Developmental aspects (including cyberbullying) - Mestre-Bach, Gemma; Fernández-Aranda, Fernando; Jiménez-Murcia, Susana; Potenza, Marc N. (Mental Health in a Digital World, 2023)
Although there is a growing interest in understanding the impact of types and patterns of Internet use on individuals of different ages, relatively few studies have fully considered developmental perspectives. This chapter offers an overview of the main findings regarding Internet use and problematic Internet use during stages of development. It includes both behavioral development and neurodevelopment and describes frequently performed online behaviors including social networking, online sex, gambling and gaming, and cyberbullying.
Keywords: adolescence; adulthood; childhood; development; neurodevelopment; problematic Internet use; Scopus(2)